Monogenic functions taking values in generalized Clifford algebras - Dinh, Doan Cong (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 512.579 Generalized Clifford algebras are constructed by various methods and have some applications in mathematics and physics. In this paper we introduce a new type of generalized Clifford algebra such that all components of a monogenic function are solutions of an elliptic partial differential equation. One of our aims is to cover more partial differential equations in framework of Clifford analysis. We shall prove some Cauchy integral representation formulae for monogenic functions in those cases.